Trypanosoma cruzi loop-mediated isothermal amplification (Trypanosoma cruzi Loopamp) kit for detection of congenital, acute and Chagas disease reactivation. - Susana A Besuschio; Albert Picado; Arturo Muñoz-Calderón; Diana P Wehrendt; Marisa Fernández; Alejandro Benatar; Zoraida Diaz-Bello; Cecilia Irurtia; Israel Cruz; Joseph M Ndung'u; María L Cafferata; Graciela Montenegro; et al. (Public Library of Science (PLoS), 2020)
A Trypanosoma cruzi Loopamp kit was recently developed as a ready-to-use diagnostic method requiring minimal laboratory facilities. We evaluated its diagnostic accuracy for detection of acute Chagas disease (CD) in different epidemiological and clinical scenarios. In this retrospective study, a convenience series of clinical samples (venous blood treated with EDTA or different stabilizer agents, heel-prick blood in filter paper or cerebrospinal fluid samples (CSF)) from 30 infants born to seropositive mothers (13 with congenital CD and 17 noninfected), four recipients of organs from CD donors, six orally-infected cases after consumption of contaminated guava juice and six CD patients coinfected with HIV at risk of CD reactivation (N = 46 patients, 46 blood samples and 1 CSF sample) were tested by T. cruzi Loopamp kit (Tc LAMP) and standardized quantitative real-time PCR (qPCR). T. cruzi Loopamp accuracy was estimated using the case definition in the different groups as a reference. Cohen's kappa coefficient (κ) was applied to measure the agreement between Tc LAMP (index test) and qPCR (reference test). Sensitivity and specificity of T. cruzi Loopamp kit in blood samples from the pooled clinical groups was 93% (95% CI: 77-99) and 100% (95% CI: 80-100) respectively. The agreement between Tc LAMP and qPCR was almost perfect (κ = 0.92, 95% CI: 0.62-1.00). The T. cruzi Loopamp kit was sensitive and specific for detection of T. cruzi infection. It was carried out from DNA extracted from peripheral blood samples (via frozen EDTA blood, guanidine hydrochloride-EDTA blood, DNAgard blood and dried blood spots), as well as in CSF specimens infected with TcI or TcII/V/VI parasite populations. The T. cruzi Loopamp kit appears potentially useful for rapid detection of T. cruzi infection in congenital, acute and CD reactivation due to HIV infection.